2017
DOI: 10.1002/jcb.26263
|View full text |Cite
|
Sign up to set email alerts
|

Eribulin regresses a doxorubicin‐resistant Ewing's sarcoma with a FUS‐ERG fusion and CDKN2A‐deletion in a patient‐derived orthotopic xenograft (PDOX) nude mouse model

Abstract: Ewing's sarcoma is a recalcitrant tumor greatly in need of more effective therapy. The aim of this study was to determine the efficacy of eribulin on a doxorubicin (DOX)-resistant Ewing's sarcoma patient derived orthotopic xenograft (PDOX) model. The Ewing's sarcoma PDOX model was previously established in the right chest wall of nude mice from tumor resected form the patient's right chest wall. In the previous study, the Ewing's sarcoma PDOX was resistant to doxorubicin (DOX) and sensitive to palbociclib and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
(100 reference statements)
1
11
0
Order By: Relevance
“…We established PDOX models of all major cancer types [9-11, 14, 18-23, 27-31]. The PDOX model has great potential for precision personalized therapy of cancer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We established PDOX models of all major cancer types [9-11, 14, 18-23, 27-31]. The PDOX model has great potential for precision personalized therapy of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Mouse housing, feeding, surgical processes, and imaging were conducted as previously described [9-11]. The mice were humanely sacrificed as previously described [9-11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarcoma is a group of 50 or more rare recalcitrant cancers [ 1 ]. In order to improve the outcome of sarcoma patients, we have developed patient-derived orthotopic xenograft (PDOX) models of the major sarcomas: soft-tissue sarcoma [ 2 – 4 ], follicular dendritic-cell sarcoma [ 5 ], Ewing’s sarcoma [ 6 10 ], undifferentiated pleomorphic soft-tissue sarcoma [ 11 , 12 ], osteosarcoma [ 13 16 , 25 ], rhabdomyosarcoma [ 17 , 18 ], leiomyosarcoma [ 19 ] and undifferentiated spindle-cell sarcoma (USCS) [ 20 , 23 , 26 ]. During the course of finding more efficacious agents for this group of diseases, we have found that our developmental therapeutic, recombinant methioninase (rMETase), is active and can inhibit or arrest tumor growth and in combination with an appropriate chemotherapy drug, can regress the PDOX tumors [ 7 , 21 26 ].…”
Section: Introductionmentioning
confidence: 99%